Adequacy of hemodialysis in end stage renal disease patients at a tertiary care hospital - Dilawar, Mubashir; Bhatti, Shehrbano; Mansoor Ahmed, Ateka; Hashmi, Abdullah; Roof Kamran, Abdur; Ikram, Zubda (Pakistan Journal of Kidney Diseases, 2025)
Hemodialysis helps to reverse uremic signs and symptoms in chronic kidney disease Stage 5 patients. It improves patients’ general well-being and nutritional status. For effective hemodialysis, adequacy should be checked routinely. Urea Reduction ratio and KT/V are the methods most commonly used to assess adequacy of hemodialysis. Objective: This study was done to evaluate urea reduction ration (URR) as a marker of adequacy of dialysis. Methods: Prospective observational study was during the month of march 2025 to calculate the URR of 50 maintenance hemodialysis patients. statistical analysis was done to explore relationship between URR and continuous variables. Results: majority were males (70%) and mean age was 53.4 ± 14.2 years. A negative correlation was noted between age and URR Almost all 92% of the patients achieved the URR target of 65%. Conclusion: Our study patients achieved the target URR in majorityof the patients and higher age was associated with a lower URR value.